Retinitis Pigmentosa and Bilateral Idiopathic Demyelinating Optic Neuritis in a 6-Year-Old Boy with OFD1 Gene Mutation - Xun Wang; Cong Zheng; Wen Liu; Hui Yang (Case Reports in Ophthalmological Medicine)
To identify the cause of a sudden binocular vision decrease in patients with retinitis pigmentosa and bilateral idiopathic demyelinating optic neuritis is difficult, but early diagnosis and treatment significantly improve the prognosis. Here, we report a 6-year-old boy with a progressive binocular vision decrease in 38 days. The patient had a history of night blindness, a mottled retina without pigmentation, extinguished electroretinographic response, tritanopia, and an absent ellipsoid zone outside the macula fovea by optical coherence tomography in both eyes. His condition was diagnosed as retinitis pigmentosa (RP) with idiopathic demyelinating optic neuritis (IDON). After corticosteroid therapy, visual acuity recovered to OD: 0.5 and OS: 0.4. Genetic analysis revealed a G985S variant in the oral-facial-digital syndrome 1 gene. Ophthalmologists should pay attention to the existence of other complications in patients with RP who suffer a sudden decrease in vision. A gene survey can help clarify this diagnosis. To our knowledge, this is the first report of a patient with RP and ON, as well as genetic testing results. Nevertheless, the pathogenicity of the variant needs further confirmation.